Overreaching, the overtraining syndrome and recovery - Halson, S. (World book of swimming: From science to performance, 2012)
The high volume nature of elite swim training can result in an increased susceptibility to overreaching and the overtraining syndrome. Appropriate use of recovery strategies during training and competition may result in reduced fatigue, enhanced adaptation to training and reduced risk of developing the overtraining syndrome. Appropriate monitoring of performance and mood state may provide early indications of excessive fatigue. Biochemical, hormonal and immune system indicators appear to be less promising as markers of overreaching and the overtraining syndrome. Both active and passive recovery can be beneficial to repeat performance when considering the duration of the effort and the amount of recovery time. Further, evidence regarding the effectiveness of various recovery strategies, including hydrotherapy and sleep quality and quantity, is increasing. Research is supporting the role of recovery in minimising fatigue associated with high intensity training. A careful balance of appropriate high volume training and recovery can ensure maximum performance gains arc achieved by elite swimmers. Monitoring of the swimmers' performance and mood state and incorporating recovery strategies can play a role in ensuring this balance is maintained.